ANALISIS KOMPETENSI PROFESIONAL GURU DALAM PERSPEKTIF UNDANG-UNDANG DAN TANTANGAN PENDIDIKAN MODERN - Zahwa Nabilah Pasya; Syahrun Nizam Udin; Munawir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Teachers play an important role in the success of national education, but the problems faced continue to change over time. This article aims to analyze how teacher professional competence is constructed based on Law Number 14 of 2005 concerning Teachers and Lecturers, and Government Regulation Number 19 of 2005 concerning National Education Standards. In addition, this study identifies the difficulties faced by teachers in meeting these competency demands in the era of modern education. This study uses a qualitative approach and library research method, with data sources in the form of educational regulations, government policies, and relevant scientific literature. The findings show that although current regulations have provided a fairly strong normative framework for four dimensions of teacher competence: pedagogical, personal, social, and professional, implementation remains limited. The main problems lie in the limited digital resources of teachers, quality gaps between regions, and the lack of consistent and relevant training programs.